Penerapan Strategi Guru Terhadap Speech Delay Anak di Taman Kanak-Kanak negeri pembina 01 Linggo Sari Baganti - Anatasya, Dika; Nurhafizah; Farida Mayar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language development plays a crucial role in enabling young children to communicate, express their thoughts, and interact with their surroundings. However, not all children develop language skills according to their developmental milestones. One common language disorder is speech delay, a condition in which children's speech development is below the expected level for their age, resulting in difficulties in pronouncing words clearly, responding to verbal communication, and understanding simple instructions. Preliminary observations conducted at TK Pembina 01 Linggo Sari Baganti identified three children with speech delay, highlighting the need for appropriate teaching strategies to support their language development. This study aimed to analyze teachers' strategies for addressing speech delay in early childhood education. A qualitative case study approach was employed. The research participants consisted of three children with speech delay, while two classroom teachers served as the key informants. Data were collected through observations, interviews, and documentation and analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that the children experienced delayed expressive language development, characterized by unclear pronunciation, limited vocabulary, difficulty responding to verbal communication, and challenges in understanding simple instructions. To address these difficulties, teachers implemented three complementary strategies: a caring approach to build children's emotional security and self-confidence, the use of illustrated storybooks to stimulate language development, and a learning center model that encouraged active communication and social interaction. It can be concluded that an integrated and sustained learning strategy can support the development of speaking skills in children with speech delays.